A critical examination of research narratives 'rumours' and passive community resistance in medical research. Issue 4 (22nd April 2022) - Nyirenda, Deborah; Sariola, Salla; Desmond, Nicola
Abstract : Several studies in Africa have reported effects of 'rumours, misconceptions or misinformation' on medical research participation and uptake of health interventions. As such, community engagement has sometimes been used for instrumental purposes to enhance acceptability of research or interventions and prevent 'rumours'. This paper seeks to highlight the value of ongoing engagement with communities to understand research narratives 'rumours' reproduced in medical research. We demonstrate that 'rumours' are a form of divergent communication or local interpretation of medical research that needs critical attention, and we question the ethics of dismissing such divergent communication. This paper draws on experiences from ethnographical research, which aimed to understand community engagement in medical research projects conducted in Malawi. We observed that even though community meetings were held to improve participation, 'rumours' about research influenced decision making. 'Rumours' presented local critiques of medical research, legitimate concerns informed by historical experiences and local conceptualisation of health. Structural inequalities, negative outcomes or absence of visible benefits following research participation informed unmet expectations, discontent with research and consequently passive resistance. The sociocultural context where participating research communities often rely on social networks for information nurtured propagation of these divergent perspectives to inform lay discourse around medical research. We conclude that ongoing engagement, critical self-reflection and attempts to decode deeper meaning of 'rumours' throughout research implementation is necessary, to show respect and address community concerns expressed through 'rumours', enhance informed participation and adoption of future health interventions.